Zloženke med skladnjo in leksikologijo - Štumberger, Saška (Jezik in slovstvo, 2018)
The syntactical relations in compounds are most clearly revealed in deverbal compounds in which, when involving a transformation into an infixal morpheme, the following syntactical relations can be recognised: rection, subject-predicator agreement, combination of verb and noun with no case expressed, and word combinations with a predicative modifier. In nominal compounds, the infixal morpheme can be the result of a transformation of a subordinate or coordinate syntactical relation. The research material indicates a far greater presence of subordinate compounds. A German study of our understanding of nominal compounds shows that, in denominal compound nouns, there are no clear criteria for distinguishing between coordinate and subordinate compounds. Research on whether Slovenian speakers distinguish between coordinate and subordinate nominal compounds has not been carried out; however, the lack of consistency in specialised literature, orthographies, dictionaries and texts demonstrates that the distinction between coordinate and subordinate compounds is less strict than conveyed in current language manuals.
Keywords: besedotvorje; leksikalizacija; medponski morfem; morfologija; skladnja; slovenščina